Unraveling taste enhancement mechanism of yeast-inoculated reduced-salt fermented sausage: Proteolysis, taste compound formation, and receptor binding of potential salty/salty taste-enhancing peptides - Dewei Huang; Gaoxin Feng; Iftikhar Hussain Badar; Bayierta Bayinbate; Junhan Fan; Baocai Xu; Linwei Yang; Qianqian Yu; Yingying Hu; Lang Zhang (Food Microbiology, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Novel Hepatopancreas-Predominant C-Type Lectin (LvCTL) Contributes to Resistance Against Vibrio parahaemolyticus in Shrimp Litopenaeus vannamei - Ning Fu; Mengxin Xing; Yuyu Wang; Linwei Yang; Di Wang; Taolin Fan; Bang Xiao; Shengwen Niu (Fishes, 2026)
C-type lectins (CTLs) are important pattern recognition receptors (PRRs) involved in innate immune defense in crustaceans. In this study, a novel C-type lectin, designated LvCTL, was identified and functionally characterized from Litopenaeus vannamei. Sequence analysis revealed that the open reading frame (ORF) of LvCTL is 495 bp in length and encodes a 164-amino acid polypeptide containing a typical C-type lectin-like domain but lacking the classical carbohydrate-binding motifs. Notably, two novel EPF motifs were identified in the CTLD region, suggesting a potential non-canonical ligand recognition pattern. Phylogenetic analysis revealed that LvCTL clustered with other crustacean CTLs. Tissue expression analysis revealed that LvCTL exhibited the highest transcript level in the hepatopancreas. After immune stimulation, LvCTL expression in the hepatopancreas was significantly regulated by LPS, Vibrio parahaemolyticus, Staphylococcus aureus, WSSV and Poly(I: C), indicating its involvement in antimicrobial immune responses. RNA interference assays showed that knockdown of LvCTL significantly increased the bacterial burden and reduced the survival rate of shrimp after V. parahaemolyticus infection. Furthermore, recombinant LvCTL displayed broad bacterial binding activity to Gram-negative and Gram-positive bacteria and induced calcium-dependent agglutination of V. parahaemolyticus and S. aureus. Taken together, these results demonstrate that LvCTL functions as an important immune recognition molecule and contributes to antibacterial defense against V. parahaemolyticus in L. vannamei. These findings broaden our understanding of the functional diversity of shrimp CTLs and their contributions to crustacean innate immunity.

Two unusual stereoisomeric dammarane-type triterpenoid saponins from the leaves of Panax japonicus (T. Nees) C. A. Mey - Yezi Ma; Linwei Dan; Wei Wang; Yuze Li; Xiaomei Song; Hao Fan; Dongdong Zhang (Natural Product Research, 2026)

Warming increases viral diversity and the relative abundance of virulent viruses in deep soils - Yiqing Lv; Xiaomin Fan; Xiangyu Fan; Wenkuan Qin; Xudong Wang; Xin Sun; Biao Zhu; Linwei Wu (Soil Biology and Biochemistry, 2026)

SFMT-Net: Underwater image enhancement framework with Multi-Scale spatial-Frequency matching transformation network - Boliang Guan; Guancheng Chen; Linwei Fan; Jintao Song; Xiaonan Luo (Ocean Engineering, 2026)

Metagenomic insights into the global distribution and functional potentials of major polyphosphate-accumulating organisms (PAOs) in activated sludge wastewater treatment plants - Zhenhui Yang; Yi Yang; Daliang Ning; Xiaomin Fan; Yiqing Lv; Linlan Zhuang; Linwei Wu (Water Research, 2026)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts - Junlin Chen; Yaqi Fan; Xingguo Zhang; Zimeng Yuan; Hairu Zhang; Xinglian Xu; Jun Qi; Guoyuan Xiong; Lin Mei; Yuan Zhu; Linwei Yang; Chao Li (Food Chemistry, 2023)